Os problemas de transporte energético da Chesf e de seu combate fulminante a possíveis incêndios - Soares, Antônio Márcio de Lima (2023)
Mathematics as one of the main sciences in the construction of one or more strategic decisions to be taken in different daily lives of humanity defined the present research. Its main objective was related to the search for the optimization of procedures operations for transporting electricity and assigning personnel in a specific firefighting action at hydroelectric complex of Companhia Hidro El´etrica do S˜ao Francisco (Chesf), located in the city of Paulo Afonso/BA. In this sense, as an investigation applied to a certain reality, now equipped with significant reflections on the numerical and non-numerical information collected, we established the quali-quantitative profile as the modus operandi of our study. And, as for the results obtained, we solved two linear programming problems associated with the procedures mentioned above, using the Simplex method, thus bringing relevant decision-making consequences for Chesf. In addition, we also carried out highlights on the practice of Mathematics teachers in basic and higher education around the study of optimization problems.